Co-infection with SARS CoV-2 and dengue virus with thrombocytopenia: A first case report from Nepal - Maharjan, Sunil; Maharjan, Elina; Bista, Bidesh (Journal of Gandaki Medical College-Nepal, 2022)
Co-infection of COVID-19 with dengue infection is quite challenging to differentiate due to it’s overlapping clinical and laboratory manifestations. We report a 22-year-old female with presented to Civil Service Hospital, emergency department with complaints of persistent fever with multiple episodes of vomiting, headache and myalgia. On examination, she was ill-looking, dehydrated with a low blood. Reverse transcriptase – polymerase chain reaction of nasopharyngeal swab detected SARS CoV-2, and dengue antibodies IgM detected. She was conservatively managed in COVID-high care unit with regular laboratory monitoring of platelet level and discharged after ninth day of admission.